2020
DOI: 10.1080/00207721.2020.1829167
|View full text |Cite
|
Sign up to set email alerts
|

High-order fully actuated system approaches: Part I. Models and basic procedure

Abstract: The state-space approaches have stayed in an absolutely dominant position in the field of systems and control for over a half century. Although a state-space representation is more suitable for deriving the state-response solution and observation (estimation), it does not provide as much convenience as desired for the control problem. In this paper, the concept of high-order fully actuated (HOFA) systems is firstly revisited, and it is pointed out that HOFA systems serve really as models for control systems ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 269 publications
(71 citation statements)
references
References 21 publications
0
71
0
Order By: Relevance
“…where m ≥ 1 is some integer, x ∈ R n and u ∈ R r are respectively the state and control vectors. It is shown that the system, when n is a multiple of r, can also be converted, under certain conditions, into a similar strict-feedback form of order m (Duan, 2020d), which reduces to the normal SFS form of (10) in the case of m = 1. Such facts indicate, from the theoretical aspect, that SFSs are a type of very common nonlinear systems.…”
Section: Typical Sfssmentioning
confidence: 99%
See 3 more Smart Citations
“…where m ≥ 1 is some integer, x ∈ R n and u ∈ R r are respectively the state and control vectors. It is shown that the system, when n is a multiple of r, can also be converted, under certain conditions, into a similar strict-feedback form of order m (Duan, 2020d), which reduces to the normal SFS form of (10) in the case of m = 1. Such facts indicate, from the theoretical aspect, that SFSs are a type of very common nonlinear systems.…”
Section: Typical Sfssmentioning
confidence: 99%
“…Very recently, it is pointed out, and also fully evidenced, in Duan (2020aDuan ( , 2020bDuan ( , 2020d) that the commonly used first-order state-space models are, although very convenient for problems of state solutions and observations, not effective enough for nonlinear system control, while the type of HOFA system models, proposed in Duan (2020aDuan ( , 2020d, are more effective and convenient for control design of nonlinear systems. It is shown in Duan (2020aDuan ( , 2020d that, once a HOFA model for a nonlinear system is obtained, the controller can then be immediately written out, which eliminates the nonlinearities in the system, and eventually results in a constant linear closed-loop system.…”
Section: Hofa System Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be used to deal with the control problem of dynamical systems, but is not the best choice. It was the preconceived occurrence which made it so popular, while it does have certain limitations in dealing with the control of dynamical systems (Duan, 2020a(Duan, , 2020b(Duan, , 2020c.…”
Section: Introductionmentioning
confidence: 99%